KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN KINERJA PROFESIONAL GURU - Rahmawati, Fitri Dwi; firdaus, Adhy; Saksana, Joned Ceilendra; Azzahra, Sitti Aliyah; Sari, Ratna; Saputra, Wisnu (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2023)
This research employs a descriptive qualitative approach. Data collection was carried out through observation, interviews, and documentation. The data analysis techniques used are the triangulation of data collection methods and location triangulation. This study discusses the leadership of the principal of SDIT ASSAMAN in enhancing the professional performance of teachers. The issue identified is that teachers, as the driving force of education, have not yet mastered technology, leading to frequent delays and setbacks in the learning process compared to other schools. The research involves 5 informants, consisting of the principal, teachers, and staff. The findings indicate that teachers' lack of technological proficiency is not the sole factor hindering education in the school. The improvement in the quality of education is driven by the collaboration between the principal, teachers, staff, and parents. All elements within the institution are integrated in realizing the school's vision and mission. The principal regularly conducts supervision and coordination, ensuring that the teaching and learning activities run effectively.